Performance comparison of permafrost models in Wudaoliang Basin, Qinghai-Tibet Plateau, China - YIN Guo-an; NIU Fu-jun; LIN Zhan-ju; LUO Jing; LIU Ming-hao (Journal of Mountain Science, 2016)
Knowledge of the spatial distribution of permafrost and the effects of climate on ground temperature are important for land use and infrastructure development on the Qinghai-Tibet Plateau (QTP). Different permafrost models have been developed to simulate the ground temperature and active layer thickness (ALT). In this study, Temperature at Top of Permafrost (TTOP) model, Kudryavtsev model and modified Stefan solution were evaluated against detailed field measurements at four distinct field sites in the Wudaoliang Basin to better understand the applicability of permafrost models. Field data from 2012 to 2014 showed that there were notable differences in observed ground temperatures and ALTs within and among the sites. The TTOP model is relatively simple, however, when driven by averaged input values, it produced more accurate permafrost surface temperature (Tps) than the Kudryavtsev model. The modified Stefan solution resulted in a satisfactory accuracy of 90%, which was better than the Kudryavtsev model for estimating ALTs. The modified Stefan solution had the potential of being applied to climate-change studies in the future.Furthermore, additional field investigations over longer periods focusing on hydrology, which has significant influence on permafrost thaw, are necessary. These efforts should employ advanced measurement techniques to obtain adequate and extensive local parameters that will help improve model accuracy.